Pengaruh Rorak Terhadap Serangan Hama Pada Tanaman Kopi Robusta (Coffea Robusta L.) - Ahmad Faizin; Canggih Nailil Maghfiroh (AGROSAINTIFIKA, 2023)
Robusta coffee (Coffea robusta L.) is one of the plantation commodities that has a very high economic value among other crops and coffee plays a very important role for the country's source of income. The Wonosalam area, Jombang Regency, has many types of coffee and the types of coffee in the Wonosalam plantations are very complete, ranging from Arabica, Robusta, and Excelsa. All three types thrive together, in one expanse. The various types of coffee bring distinct advantages for coffee farmers. One of the coffee plants that influence coffee production is the application of coffee cultivation techniques, for example by making dead-end trench, for the decomposition process. In this study, we will examine the effect of dead-end trench on pest attacks on coffee plants, in order to produce quality productivity. This research was carried out in the Wonosalam sub-district, Jombang Regency. This research was carried out directly in the field using a Completely Randomized Block Design (RAKL). The effect of using dead-end trench on pest attacks on Robusta coffee is not much different from the treatment without using dead-end trench, this is caused by several factors, including the influence of ambient temperature, humidity, wind speed and light intensity.